Collecting Quran according to these orientalist`s opinion as an example Theodor Noldke and Regis Blachere) for example Critical inquiry (Raparin Journal of Humanities (RJH), 2024)
Orientalism is an academic and scientific process which the Western people try to find out about Eastern people, They are studing  in most of these fields (economic, social, political and religion),  It is an inseparable part in conflict and the historical connection between the Eastern and Western, Quran as a holy book of the muslims which the  Orientalists had the most studing and writing about Quran, They talked about most of the to pics about Quran, In this may they created many douts, They deviated from the scientific and visionable way both of these two Orientalists (Theodor Noldke and Regis Blachere), they did a great job on Quran had been collected in three stages, at the times of the proper Muhammad(peace be upon him) and at the time of the two Rashidin Kalifas (Abubakir Alsadiq and Osman Ibn Al Hafan), It is important that the the Original historical resources had presented the way and features of collecting Quran clearly and without any douts, but both of these two Orientalists they presented their opinon on this subject, which their purpose was to create suspicion and misleading historical and scientific facts, same times, they depended on weak, resources and fabricated statements, Our goal in our studing is to show their suspicions by depending on original resources, logical and scientific evidence, we talked about their censures on their opinions